Microsoft Outlook 2010 plain & simple - Boyce, Jim, 1958- (Published with the authorization of Microsoft Corp. by O'Reilly Media, 2010)
"With this full color, no-nonsense guide, you'll learn the quickest ways to solve a problem or learn a skill with Microsoft® Outlook® 2010. Easy-to-follow steps and concise, straightforward language make learning plain and simple!"--Resource description page.